PENINGKATAN KETERAMPILAN MENULIS PANTUN MURID KELAS V MELALUI MODEL PEMBELAJARAN TGT (TEAMS GAMES TOURNAMENT) DENGAN FLASH CARD PANTUN DI SD NEGERI SUKUN 3 MALANG - Angella Caroline Serafika; Nur Kumala, Farida (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This classroom action research was motivated by the low skills of writing pantun among fifth-grade students of SDN Sukun 3. Initial observations showed that most students had difficulty in determining themes, composing interrelated rhymes and content, using appropriate rhymes, and choosing appropriate diction, resulting in pantuns that did not meet the rules of pantun. In addition, the learning process, which was still dominated by conventional methods, resulted in suboptimal student participation and motivation. This study aimed to improve fifth-grade students' pantun writing skills through the implementation of the Teams Games Tournament (TGT) learning model assisted by pantun flash cards. This study used the Kemmis and McTaggart Classroom Action Research approach, which was implemented in two cycles, with each cycle including planning, action implementation, observation, and reflection. The subjects were 28 fifth-grade students of SDN Sukun 3. Data collection techniques included pantun writing skills tests, observations of teacher and student activities, documentation, and field notes. Data were analyzed using quantitative and qualitative descriptive techniques to determine improvements in student learning outcomes and activities in each cycle. Based on the research results, it can be concluded that the implementation of the Teams Games Tournament (TGT) learning model assisted by pantun flash cards is effective in improving the pantun writing skills of fifth-grade students at SDN Sukun 3. This learning model is able to create an active, fun, competitive, and collaborative learning atmosphere so that it can be used as an alternative for learning Indonesian in pantun writing material in elementary schools.